STUDI TATA RUANG KOTA RANCANGAN VAN DER PIJL KASUS: KOTA BANJARBARU, KALIMANTAN SELATAN - Naimatul Aufa; Pakhri Anhar (TATALOKA, 2012)
Banjarbaru city is a city designed by an architect named Van der Pijl in 1953. The city was originally planned as the capital city of Kalimantan province, replacing the city of Banjarmasin. This plan was canceled and finally became forgotten, unclear, blend with the development of the city. It worsens by the loss of historical records this city. This study aims to determine how the spatial planning of Banjarbaru City by Van der Pijl. This study used naturalistic research paradigm that aims to discover patterns to be developed into research results. Based on the analysis, it is found that the plan of Banjarbaru City by Van der Pijl has similarities with the concept of cities designed at the beginning of the 20th century, the concept of creating a new town outside the city, on  pristine environment with quiet atmosphere and natural environment. This concept is known as the garden city concept introduced by Ebenezer Howard. The similarity of this pattern is there have a city center as the area of governance, there is a green open spaces (parks), and there are areas designated as  residential areas located adjacent to an office area, industrial area and comercial area